Legal Counseling in Increasing Public Understanding as an Effort to Prevent Narcotics Crime in Bantan Timur Village - Trisna, Wessy; Magda, Marianne; Andriati, Syarifah Lisa; Sitepu, Faradila Yulistari (Talenta Publisher, 2021)
The increasing abuse of Narcotics in Indonesia is increasingly widespread and almost impossible to prevent. Therefore, it is necessary to increase understanding by all parties in eradicating the circulation of Narcotics. In the Narcotics Criminal Act emphasized the role of the community to actively participate in fighting narcotics crimes. For this reason, it is necessary to provide legal counseling to the public in providing an understanding as an effort to prevent narcotics crime, especially in Bantan Timur Village, Medan Tembung District, so that the public can understand how terrible and dangerous it is due to narcotics abuse. Community service is expected to contribute to the people of Bantan Timur Village both theoretically and practically in preventing the rampant circulation of narcotics. The approach method used in community service activities is: in the form of outreach to the community about prevention of narcotics control and a participatory approach, meaning that participants are required to be active in participating during the activity. The output of this activity, in addition to increasing public knowledge about the dangers of narcotics and efforts to prevent narcotics control in East Bintan Village, also provides valuable information and solutions that drugs, apart from having an impact on law violations, also have an impact on medical and psychological problems.